The Effectiveness of Karamunting Leaf’s Fraction (Rhodomyrtus tomentosa (Aiton) Hassk) as Antimicrobials in Carbapenemase Resistant Klebsiella pneumonia - Sabrina, Tia; Kamaluddin, MT; Theodorus, Theodorus; Salni, Salni (Fakultas Kedokteran Universitas Sriwijaya, 2021)
In the world, the incidence of nosocomial infections in hospitals had increased. There had been an increase in the incidence of infections caused by Enterobacteriaceae, one of them is Klebsiella pneumonia, which resistant to carbapenem in the worldwide. The consequences of increased rates of resistance to many drugs pose a high need for the discovery of new types of antibiotic drugs. Rhodomyrtus tomentosa (aiton) hassk has an antibacterial effect that has long been used by Indonesians as a traditional drug. This study aims to find out the effectiveness of karamunting leaf fraction as an antimicrobial in carbapenemase resistant K.pneumonia bacteria and to find out the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of the active compound of karamunting leaves as antimicrobial in Carbapenemase resistant Klebsiella pneumonia (CRKP) bacterial isolates. This research was an experimental laboratory research in vitro that exploratory analytical. The results of the study obtained the value of MIC ethyl acetate fraction started at a concentration of 125 μg/ml and n-hexan fraction at a concentration of 4000 μg/ml. MBC value was 125 μg/ml for ethyl acetat fraction and n-hexan fraction of karamunting leaves was 8000 μg/ml. From the bacterial activity test obtained at a concentration 32000 μg/ml of n-hexan fraction, the average diameter of the inhibitory zone 7.80 ± 1.30 mm and ethyl acetate fraction at a concentration of 4000 μg/ml can inhibit the growth of CRKP bacteria with an average of inhibition zone diameter was 9.40 ± 1.67 mm. From the results of the analysis using the Independent T Test and mann whitney test obtained a probability value between all groups with positive control was <0.05. It can be concluded that the ethyl fraction of acetate and n-hexan leaves of karamunting leaves contains active compounds that can interfere with the integrity of CRKP bacterial cell walls or membranes so that the bacteria can die.